Achieving efficient location privacy protection based on cache - Lu-lu LI; Jia-feng HUA; Sheng WAN; Hui ZHU; Feng-hua LI (Tongxin xuebao)
With the development of mobile Internet and the popularization of intelligent terminals,location based services(LBS) has been widespread in navigation,social network and other fields.Due to the sensitivity of personal location information,data privacy protection related to location of mobile objects has become the hotspots of research.Considering the openness of the background information,and based on the information cache mechanism,a dummy selection algorithm was proposed to reduce the number of interactions between the user and the untrusted server and combine the k-anonymity to achieve efficient location privacy.Without relying on trusted third party,the scheme can prevent the attackers owned background information from inference attack,and the detail simulation results indicate its effectiveness and efficiency.